Sedimentology and stratigraphy of the type section of the Pennsylvanian Boss Point Formation, Joggins Fossil Cliffs, Nova Scotia, Canada - Rygel, Michael; Lally, Corinne; Gibling, Martin; Ielpi, Alessandro; Calder, John; Bashforth, Arden (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2015)
ABSTRACT The 1125-m-thick type section of the Pennsylvanian Boss Point Formation is well exposed along the shore of the Bay of Fundy in Nova Scotia. We provide the first comprehensive account of the entirety of this formation, which comprises nearly one-third of the stratigraphic thickness of the Joggins Fossil Cliffs UNESCO World Heritage Site. The basal Chignecto Bay Member (0–91.5 m) is composed of redbeds, single-storey channel bodies with northerly paleoflow, and thin palustrine limestones. The middle Ward Point Member (91.5–951.7 m) contains up to 16 megacycles composed of alternations between thick packages of braided fluvial sandstone and fine-grained deposits. Although regional studies of the Boss Point Formation suggest that the fine-grained deposits are largely composed of lacustrine sediments, these intervals consist largely of poorly drained and well-drained floodplain deposits in the type section. The facies variations and southeast-directed paleoflow in the Ward Point Member record modest uplift associated with the growth of the salt-cored Minudie Anticline. The North Reef Member (951.7–1125 m) is composed of redbeds and two distinctive multistorey channel bodies. This uppermost member records a shift to more arid, oxidizing conditions, was the precursor to a major phase of salt withdrawal, and represents a transition to the overlying Little River Formation. The sedimentological framework, revised stratigraphy, and detailed measured section and map will provide a foundation for future study of this remarkable Pennsylvanian exposure.